PENGARUH PENGGUNAAN LEMBAR KERJA SISWA (LKS) SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PEREDARAN DARAH MANUSIA DI KELAS XI MIA SMA NEGERI 1 BANDAR PULAU TAHUN AJARAN 2021/2022 - Melinda Sari Sidauruk, Ade; Dianti Siboro, Thiur (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2022)
This study was conducted with the aim of determining the Effect of Using Student Worksheets (LKS) as a Learning Medium on Student Learning Outcomes in the Human Circulatory System Material in Class XI MIA of SMA Negeri 1 Bandar Pulau in the 2021/2022 Academic Year. The total population of class XI students was 113 students consisting of four classes and a sample of 50 students (2 classes) was taken randomly with purposive sampling. The research instrument used in data collection was a pre-test and post-test to determine the biology learning outcomes of class XI students of SMA Negeri 1 Bandar Pulau. From the results of hypothesis testing with the t-test, it was obtained |thitung| = 11.163. While ttable for df = 24, with a significance level of α = 0.05 is 2.064. So it can be concluded that |thitung| > ttable, namely 11.163 > 2.064, it can be concluded that Ha is accepted, H0 is rejected. This indicates a significant effect of the use of Student Worksheets on student biology learning outcomes. Based on the results of the Independent Sample Test, comparing the post-test scores of both classes, the significance value was 0.000 < 0.05. This concludes that there is a difference in the learning outcomes of students taught using Student Worksheets as a learning medium compared to those taught without them. The significant difference between the two scores can be seen from the average post-test scores. The test results showed that the average post-test score for the experimental class was 79.00, while the average post-test score for the control class was 61.60. The significant difference in the average scores between the experimental and control classes was 17.40.